(untitled) (Iranian Journal of Kidney Diseases, 2021)
Introduction. Idiopathic Nephrotic Syndrome is a multifactorial disease that accompanying with immune system dysfunction. Cytokines as potent immunomodulators have a key role in pathogenesis of the disease. We aimed to evaluate the association between TNFα -308G > A polymorphism with Idiopathic Nephrotic Syndrome and its effect on the response to steroid therapy. Methods. This case-control study was performed on 168 patients with Nephrotic Syndrome and 153 healthy children. Genotyping of TNF-α rs1800629 (-308G > A) variant was detected by polymerase chain reaction restriction fragment length polymorphism method (PCR-RFLP). Results. The results revealed that there was no significant difference in allele (P > .05, OR = 0.92, 95% CI: 0.59 to 1.43) or genotype (P > .05, OR = 1.00; 95% CI: 0.62 to 1.65) frequency of TNF-α rs1800629 (-308G > A) between childhood cases of nephrotic syndrome and healthy controls. Also no association was found between genotype (P > .05, OR = 2.28; 95% CI: 1.03 to 5.04), and allele frequency (P > .05, OR = 1.93; 95% CI: 0.97 to 3.87) among the SSNS and SRNS groups. Conclusion. Our results did not support any association between the TNF polymorphism and the risk of nephrotic syndrome in a sample of southeast Iranian population.